2019
DOI: 10.1016/j.immuni.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Atlas of Intestinal Immune Cells Reveals that Neuropeptide α-CGRP Modulates Group 2 Innate Lymphoid Cell Responses

Abstract: Highlights d scRNA-seq reveals intestinal immune cell programs in allergic inflammation d Intestinal KLRG1 + ILC2s express a-CGRP and its receptors d a-CGRP regulates type 2 cytokine production of KLRG1 + ILC2s d a-CGRP maintains KLRG1 + ILC2 homeostasis and the type 2 immune machinery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(173 citation statements)
references
References 83 publications
3
148
1
Order By: Relevance
“…The method described previously by (Xu et al, 2019) was followed to test for cell type composition changes between healthy and infected donors. Briefly, a negative binomial regression model was used to assess if the cell type composition between healthy donors and infected cells are significantly different.…”
Section: Identifying Viral Infected Cellsmentioning
confidence: 99%
“…The method described previously by (Xu et al, 2019) was followed to test for cell type composition changes between healthy and infected donors. Briefly, a negative binomial regression model was used to assess if the cell type composition between healthy donors and infected cells are significantly different.…”
Section: Identifying Viral Infected Cellsmentioning
confidence: 99%
“…CALCRL/Ramp1 engagement by CGRP binding triggers a signaling cascade in ILC2s, which signals via Gαs proteins and regulate intracellular cAMP levels. ILC2 activation is suppressed by CGRP and genetic deletion of components of the CGRP-CALCRL pathway resulted in elevated ILC2s responsiveness and type 2 inflammation in the context of helminth infection, lung inflammation and food allergy (40)(41)(42)(43). Other findings uncovered the regulation of ILC2s by neuroendocrine cells (94) and tuft cells that share many commonalities with neurons (Chat-expression, sensing, signal transmission).…”
Section: Innate Lymphoid Cells (Ilcs)mentioning
confidence: 99%
“…Additional neurotransmitters include, gamma-Aminobutyric acid (GABA), epinephrine and dopamine, but also vasoactive intestinal peptide (VIP), neuromedin U (NMU), calcitonin gene-related peptide (CGRP), Substance P, Galanin, Tachykinin, and others (32,35). With regard to neuronal regulation of immune responses, the biochemical signature of the neuron (neurotransmitters, neuropeptides) appear to be functionally most relevant, since many of the neuropeptides such as VIP, NMU, CGRP regulate immune responses via different subsets of immune cells (36)(37)(38)(39)(40)(41)(42)(43)(44). The in-depth characterization of enteric neurons may allow to identify neuronal subsets based on the expression of neurotransmitters/neuropeptides and to assign specific inflammatory functions analog to immune cells.…”
Section: Extrinsic Innervationmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection stimulates the production of prostaglandin D 2 which, in turn, upregulates the ILC2 response, leading to sequestration of lymphocytes into the lung and peripheral lymphopenia 34 . CGRP is an inhibitor of ILC216 , so we can infer that the lower levels of the peptide observed in COVID-19 patients would participate in worsening immune dysfunction and lymphopenia.Our immunofluorescence study showed immunoreactivity for RAMP1 in the walls of the major blood vessels, bronchi, and bronchioli, as well as in the epithelium of conducting airways. To the best of our knowledge this is the first morphological description of RAMP1 immunoreactivity in the human lung, but it coincides very closely with the location of CGRP binding sites as studied by radioactive ligand binding .…”
mentioning
confidence: 99%